Shisha use among students in a private university in Kigali city, Rwanda: prevalence and associated factors - Omoboriowo Joad Omotehinwa; Ogendi Japheths; Iyamuremye Jean Damascene; Michael Habtu (BMC, 2018)
Abstract Background All over the globe shisha smoking is fast growing among different age brackets. Shisha use has been reported to be increasing among youths in African major cities. Its use is documented to result in health effects such as lung cancer, cardiovascular and respiratory conditions, periodontal diseases, keratoacanthoma which are also associated with cigarette smoking. In Kigali, Rwanda's capital, reports indicate that shisha use is increasing among the youths, particularly the university students. The study aimed at determining the prevalence, and establishing factors associated with shisha use among students in a university in Kigali Rwanda, which will be a significant step in stemming shisha fame among youths in Rwanda as there was no previously documented evidence-based study. Methods A total of 427 students were selected for this cross-sectional study using stratified sampling method. A questionnaire was used to collect data on shisha use, knowledge about shisha, attitude towards shisha, and factors associated with use of shisha. The association between the independent variables and shisha use was assessed using chi-square p value < 0.05. Binary logistic regression was used to determine variables that were independently associated with shisha smoking. Results Prevalence of ever smoking shisha among the university students was 26.1% and that of those that smoked in the last month (30 days) was 20.8%. About 40 % (39.9%) of the participants that had heard about shisha before demonstrated low level of knowledge, and 41.6% of these reported shisha use in the last 30 days. Logistic regression revealed that the followings were independently associated with shisha smoking: always drink alcohol (p = 0.003); drink alcohol occasionally (p = 0.045); having friend(s) who smoke shisha (p = 0.001); being aware of shisha's availability in cafes, bars and restaurants in Kigali (p = 0.022); positive attitude towards shisha smoking (p < 0.001) and participants with age < 20 years (p = 0.039). Conclusions There is a relative high prevalence of shisha smoking and a poor knowledge about its impact on health among these university students. Regular medical education and health promotion targeting the youths could improve knowledge and practices about shisha use. Shisha laws and regulations should be enacted, and fines imposed on individuals or group who flout them.